Development, optimization and improvement of ZnSe crystal surfaces mechanical and chemical treatment and washing methods - Stanetska, А.S.; Tomashyk, V.N.; Stratiychuk, І.B.; Tomashyk, Z.F.; Kravetskyy, M.Yu.; Galkin, S.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
The process of cutting, mechanical and chemical treatment of the undoped and doped ZnSe crystal surface has been studied. The chemical interaction of zinc selenide surface with bromine emerging solutions of H₂O₂ – HBr and H₂O₂ – HBr – organic solvent has been studied. The surface states after chemical etching have been investigated using electron, metallographic and atomic force microscopy, and it was shown that the surface state is improved after chemical etching. Etchant selection to develop slow polishing compositions for chemical-mechanical polishing of investigated materials has been made. Efficient methods for washing samples solutions have been developed after different types of ZnSe surface treatment: cutting of the crystal, mechanical surface treatment, chemical removing the surface damaged layer.